2010
DOI: 10.1002/hep.23875
|View full text |Cite
|
Sign up to set email alerts
|

A Novel GSK-3 beta–C/EBP alpha–miR-122–Insulin-Like Growth Factor 1 Receptor Regulatory Circuitry in Human Hepatocellular Carcinoma

Abstract: 1 miR-122 is a highly abundant, hepatocyte-specific microRNA. The biomedical significance and regulatory mechanisms of miR-122 remain obscure. We explored the role of miR-122 in tumorigenesis in the context of gene regulatory network. The miR-122 promoter and its transactivator were identified by way of luciferase reporter system, electrophoretic mobility shift, and chromatin immunoprecipitation assays. The miR-122 regulatory circuitry and its implication in hepatocarcinogenesis were identified using livers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 31 publications
1
122
1
Order By: Relevance
“…The reversely transcribed cDNA were temporarily stored in a refrigerator at −20°C. The RT‐qPCR prime sequences are displayed in Table 1 using TaqMan probes 18. The reaction system was performed according to the instructions of TaqMan RT‐PCR kit (No.…”
Section: Methodsmentioning
confidence: 99%
“…The reversely transcribed cDNA were temporarily stored in a refrigerator at −20°C. The RT‐qPCR prime sequences are displayed in Table 1 using TaqMan probes 18. The reaction system was performed according to the instructions of TaqMan RT‐PCR kit (No.…”
Section: Methodsmentioning
confidence: 99%
“…Using a genome-wide expression profiling approach, Burchard et al (2010) have recently shown decreased miR-122 expression and increased miR-122 predicted target genes in tumor tissues compared with nontumor tissues from HCC, which may possibly lead to impairment of mitochondrial metabolism. Loss of miR-122 expression in HCC, which is associated with poor prognosis and metastasis, has been confirmed by several other studies (Coulouarn et al, 2009;Bai et al, 2009;Zeng et al, 2010;Mizuguchi et al, 2011;Karakatsanis et a., 2011). In these studies, miR-122 is shown to be involved in cell proliferation, apoptosis, clonogenic survival, migration, in vivo invasion, and tumor formation in nude mice.…”
Section: Mir-122 In Hccmentioning
confidence: 53%
“…Loss of miR-122 facilitates cell tumorigenic properties such as cell migration and invasion, and restoration of miR-122 reverses this phenotype. Currently, several target genes of miR-122 have been identified to be involved in hepatocarcinogenesis, such as ADAM10 (a distintegrin and metalloprotease family 10), serum response factor (SRF) (Bai et al, 2009), insulin-like growth factor 1 receptor (Igf1R) (Zeng et al, 2010), cyclin G1 (Fornari et al, 2009), and Wnt1 (Xu et al, 2012). In addition, overexpression and restoration of miR-122 in HCC cells has been shown to sensitize HCC cells to chemotherapeutic agents (Bai et al, 2009;Xu et al, 2011;Yang et al, 2011).…”
Section: Mir-122 In Hccmentioning
confidence: 99%
“…The existence of corresponsive PP2A B56g-miR-27a-Fbxw7 regulatory axis in human lung tumors further confirms that B56g subunit is indispensable in ST-induced upregulation of miR-27a. Recently, we have demonstrated that the dysfunction of a novel GSK-3b-C/EBPa-miR-122-IGF-1R regulatory circuitry contributes to the development of hepatocellular carcinoma (Zeng et al, 2010). We identified that C/EBPa, the activity of which is controlled by the status of phosphorylation, directly binds to the promoter of the miR-122 gene and initiates transcription.…”
Section: Discussionmentioning
confidence: 99%